Sexual harassment at work: Targets’ perspectives on prevention and response - Christianne Corbett; Meghan O. Warner; Sarah J. Harsey; Jennifer J. Freyd (PLoS ONE, 2026)
Harassment, including sexual harassment, in the workplace poses a significant threat to workers’ wellbeing and contributes to social inequities. Organizations play a pivotal role in both enabling and preventing workplace harassment. We use a grounded theory approach to understand how workers experience workplace sexual harassment. Drawing on semi-structured interviews with thirty U.S. workers, most from the service industry in the San Francisco Bay Area, who have experienced sexual harassment at work, we describe organizational practices that workers believe effectively prevent and respond to harassment. Findings demonstrate that workplaces may better support workers by (1) setting clear expectations that harassment will not be tolerated and (2) responding effectively to incidents of harassment by establishing an independent entity to whom victims can report incidents, providing verbal support, and taking appropriate actions to support and protect victims.